Preliminary experience with EBA ONE intramedullary nail for the treatment of pertrochanteric fractures - Oldani, Danila; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: The Authors report their preliminary experience with a new fixation device for treatment of pertrochanteric fractures. The EBA ONE nail, produced by Citieffe in Bologna - Italy. Materials: Between April 2019 and August 2019 in Orthopedics and Traumatology Department of  Piacenza,  11 patients (all female) with stable and unstable pattern of fractures, were treated with the EBA ONE intramedullary nail. Results: Despite the limited number of cases and the assence of a complete follow-up, the initial results are very encouraging. None of the reported complications were linked to the fixation device or to the surgical technique. Conclusions: The minimal, simple and intuitive instrumentation set and the simplicity of the surgical procedure make this fixation device valuable for use in stable fractures. The possibility to distal locking the nail, either statically or dynamically, and the availability of a longer nail make this device also effective in more complex fractures.